Behavioral and Social Interaction Patterns of Children from Female Migrant Workers in Bawang, Batang - Natalia, Aryani Sari; Rusdarti, Rusdarti; Purnomo, Arif (Journal of Educational Social Studies, 2024)
The high unemployment rate in Indonesia has led many women to choose to work as female migrant workers abroad to overcome their family's economic limitations. This decision not only leads to financial improvements but also brings social changes, especially in childcare. Children abandoned by mothers who work as migrant workers often have difficulty establishing social relationships and receiving adequate emotional support. This study aims to analyze the social behavior of junior high school students in Bawang Sub-district, Batang Regency, who were abandoned by their mothers who work as female migrant workers. The research method used aqualitative approach with a case study through in-depth interviews and observations of children from female migrant workers' families. The results showed that children from female migrant families often have difficulty establishing social relationships due to the lack of direct control and emotional attention from their mothers who work abroad. The study concluded that although the mother's departure helps economically, the challenges in the care and social development of the children were issues that need to be considered. This research contributed to understanding the social impact of the female migrant worker's departure phenomenon on children's behavior.